The Activist Humanist Form and Method in the Climate Crisis - Levine, Caroline; Levine, Caroline (Princeton University Press, 2023)
An argument that humanists have the tools$1 (Band the responsibility$1 (Bto mobilize political power to tackle climate changeAs climate catastrophes intensify, why do literary and cultural studies scholars so often remain committed to the separation of aesthetic study from the nitty-gritty of political change? In this thought-provoking book, Caroline Levine makes the case for an alternative view, arguing that humanists have the tools to mobilize political power$1 (Band the responsibility to use those tools to avert the worst impacts of global warming. Building on the theory developed in her award-winning book, Forms, Levine shows how formalist methods can be used in the fight for climate justice.Countering scholars in the environmental humanities who embrace only (3z(Bmodest gestures of care(3y$1 (Band who seem to have moved directly to (3z(Bmourning(3y (Bour inevitable environmental losses$1 (BLevine argues that large-scale, practical environmental activism should be integral to humanists$1 (Bwork. She identifies three major infrastructural forms crucial to sustaining collective life: routines, pathways, and enclosures. Crisscrossing between art works and public works$1 (Bfrom urban transportation to television series and from food security programs to rhyming couplets$1 (Bshe considers which forms might support stability and predictability in the face of growing precarity. Finally, bridging the gap between academic and practical work, Levine offers a series of questions and exercises intended to guide readers into political action. The Activist Humanist provides an essential handbook for prospective activist-scholars.s